The Influence of Socio-Cultural Approaches on Ecological Disaster Management in Lake Balang Tonjong, Makassar - Ahmad Hasyim; Fahruddin; Rahmadi Tambaru; Eymal B. Demmalino; Magdalena Litaay; Muh. Sri Yusal (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
Ecological pressures on the Balang Tonjong lake ecosystem are currently very strong due to its use as a tourist destination, community settlement, fishing, agriculture, and traditional market. All of these ecological pressures greatly affect the nature of the water, which can influence lake organisms, including gastropods. The purpose of this study was to examine the influence of socio-cultural aspects on the process of ecological disaster management in Balang Tonjong, Makassar. The study was conducted using descriptive quantitative techniques with purposive sampling at five stations considered representative of the study area. In this case, direct observation was carried out by conducting direct interviews with the community in Balang Tonjong. The results of the study indicate that socio-cultural aspects greatly influence the management of ecological disasters in Lake Balang Tonjong. This shows that the community has high awareness and participation, has more effective management knowledge and experience, and has a high appreciation for the condition of the lake and is very concerned about its preservation.